Management of Postpartum Uterine Prolapse in a Non Descript Doe with Vulval Retention Sutures - Thokala, Jayanth Sai Kumar Reddy; Keerthana, Pandiri; Krishna, Maganti Venkata Gopala; Ramana , Kudikilla Venkata (The Indian Journal of Animal Reproduction, 2025)
A case of total uterine eversion (uterine prolapse) in a doe was effectively managed, as is described. Buhner’s suture was applied to prevent a recurrence.